Supra b Limit Points and Supra b Separation Axioms (European Journal of Pure and Applied Mathematics, 2022)
In recent years, some generalized structures of topology were introduced. Supra topology was one the most important of those generalizations. To contribute in this orientation, we devoted this work to studying limit points and separation axioms on supra topological spaces by using supra $b$-open sets. We define them in a similar way of their counterparts on topological spaces. In general, we demonstrate their main properties and investigate the sufficient conditions for some equivalent relations between them. Some novel and interesting examples are provided.